Indirect / direct heterojunction MoS2 / CdS composite photocatalytic material as well as preparation method and application thereof

By controlling the ultrasonic time of MoS2 and its combination with cadmium sulfide, the energy band structure of MoS2/CdS composite materials is optimized, the problem of limited photocatalytic activity is solved, and the efficient photocatalytic decomposition of aquatic hydrogen is achieved, and the photocatalytic performance is improved.

CN119140123APending Publication Date: 2024-12-17QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)

Patent Information

Application Number
CN202411352200.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The photocatalytic activity of MoS2/CdS composite photocatalytic materials is limited by the semiconductor type and energy band distribution of MoS2, resulting in a high recombination rate of photogenerated carriers, which limits the improvement of its photocatalytic performance.

Method used

By controlling the ultrasonic time of MoS2, adjusting its transition from indirect semiconductor to direct semiconductor, and combining with cadmium sulfide, optimizing the energy band structure and inhibiting the recombination of photogenerated carriers.

Benefits of technology

It realizes efficient photocatalytic decomposition of aquatic hydrogen, improves the photocatalytic efficiency of MoS2/CdS composite materials, matches the reduction potential of the energy band position with H+, and significantly improves the photocatalytic hydrogen production performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140123A_ABST
    Figure CN119140123A_ABST
Patent Text Reader

Abstract

The invention provides an indirect / direct heterojunction MoS2 / CdS composite photocatalytic material as well as a preparation method and application thereof, and belongs to the technical field of nano composite materials. The MoS2 and the aluminum oxide abrasive are mixed, the ultrasonic time of MoS2 is changed, the type of a MoS2 semiconductor is changed, CdS is synthesized through cadmium nitrate tetrahydrate, thiourea and sodium citrate and compounded with MoS2, the MoS2 / CdS composite material with the high photocatalytic performance is obtained, the MoS2 / CdS composite material synthesized through the method is high in photocatalytic efficiency, the energy band position is matched with H + reduction potential, and the MoS2 / CdS composite material can be used for preparing the MoS2 / CdS composite material with the high photocatalytic performance. The composite photocatalyst can effectively inhibit recombination of photon-generated carriers, and has excellent photocatalytic hydrogen production performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanocomposite materials, and relates to an indirect / direct heterojunction type MoS2 / CdS composite photocatalytic material and a preparation method and application thereof. Background Art

[0002] Photocatalytic decomposition of water to produce hydrogen has great potential in solving the two major problems of environment and energy, but the low photocatalytic efficiency limits its application in actual production. Therefore, the development of photocatalysts with higher catalytic efficiency is the primary task to realize the practical application of photocatalytic decomposition of water to produce hydrogen. Cadmium sulfide (CdS), as a common photocatalyst, belongs to direct semiconductor materials, has good absorption of visible light, and is low in cost. It is an excellent photocatalyst, but the high recombination rate of photogenerated carriers of CdS leads to its low photocatalytic activity. Therefore, it is a common method to inhibit the recombination of photogenerated carriers by combining CdS with other materials. Molybdenum disulfide (MoS2) has attracted much attention due to its weak van der Waals bonds between layers, graphene-like structure and adjustable band gap. The use of MoS2 as a co-catalyst to achieve the effective separation direction of CdS photogenerated carriers has received widespread attention. However, bulk MoS2 exhibits narrow band gap indirect semiconductor characteristics. At the same time, the distribution position of the energy band is different from that of H + The reduction potential mismatch limits the further improvement of the performance of MoS2 / CdS composite photocatalytic materials. At the same time, MoS2 has the characteristic of gradually widening the band gap as the number of layers decreases, and when the number of layers becomes a single layer, MoS2 will undergo a transition from an indirect semiconductor to a direct semiconductor. Therefore, the suppression of photogenerated carrier recombination and the optimization of energy band position can be achieved by reasonably controlling the process of the semiconductor type of MoS2 from indirect to direct.

[0003] At present, there are many reports on MoS2 / CdS heterojunctions. [CN111229260A] synthesized a MoS2 / CdS heterojunction photocatalyst by first synthesizing MoS2 nanobelts with specific morphology and exposed a large number of active sites, and then loading smaller CdS nanoparticles, which effectively promoted the separation of photogenerated carriers and inhibited the recombination of photogenerated carriers. [CN105664977B] proposes a MoS2-CdS nanocomposite material, a preparation method thereof and an application in photocatalytic decomposition of water to produce hydrogen. A MoS2-CdS nanocomposite material is obtained by using nano-CdS as a carrier and in situ growing amorphous layered nano-MoS2 thereon. These studies focus on the construction of composite materials and the regulation of the morphology of composite materials, while few people have explored the related directions of adjusting the transformation of the semiconductor type of MoS2 to achieve the improvement of the photocatalytic performance of MoS2 / CdS composite materials. Therefore, it is of great significance to propose an indirect / direct heterojunction MoS2 / CdS composite photocatalytic material, which suppresses the recombination of photogenerated carriers by controlling the semiconductor type transformation of MoS2 and simultaneously optimizes the energy band structure, thereby greatly improving the activity of photocatalytic hydrogen production. Summary of the invention

[0004] The present invention aims to provide an indirect / direct heterojunction type MoS2 / CdS composite photocatalytic material and a preparation method and application thereof.

[0005] A method for preparing an indirect / direct heterojunction MoS2 / CdS composite photocatalytic material, the specific steps are as follows: (1) MoS2 and alumina abrasive were mixed, deionized water was added for ultrasonic treatment, and then the mixture was allowed to stand to collect the supernatant; (2) adding cadmium nitrate tetrahydrate, thiourea and sodium citrate to the supernatant obtained in step (1), and then adding ammonia water and deionized water in sequence, and stirring at room temperature to form a uniform solution; (3) The uniform solution was transferred to a polytetrafluoroethylene reactor, and the reactor was placed in an oven to keep warm. After natural cooling, the reactor was taken out and the obtained sample was separated by filtration, washed with deionized water for multiple times, and placed in an oven to dry to obtain a MoS2 / CdS composite photocatalytic material.

[0006] Preferably, in step (1), the mass ratio of MoS2 to alumina is 1:0.2-1:0.6, preferably 1:0.4, and the mass volume ratio of MoS2 to deionized water is 1:600-1000 g / mL, more preferably 1:800 g / mL.

[0007] Preferably, the ultrasonic time in step (1) is t, 4≤t<20, more preferably 12 h.

[0008] Preferably, the standing time in step (1) is 24-48 h.

[0009] Preferably, in step (2), the molar ratio of cadmium nitrate tetrahydrate to thiourea is 1:1-1:10, the concentration of sodium citrate in the homogeneous solution is 0.6-2 mg / mL, the volume fraction of ammonia water is 0.7-3% of the homogeneous solution, more preferably 1.3%, and the mass of MoS2 added to the supernatant should be 10-20% of the mass of the target product MoS2 / CdS, more preferably 15%.

[0010] Preferably, in step (3), the insulation temperature is 180-220°C, the insulation time is 12-24 h, the drying temperature is 70°C, and the drying time is 12 h.

[0011] The present invention also includes the use of the above-mentioned indirect / direct heterojunction type MoS2 / CdS composite photocatalytic material in photocatalytic decomposition of water to produce hydrogen.

[0012] Technical features and beneficial effects of the present invention: The present invention adjusts the change of MoS2 energy band by controlling the ultrasonic time of MoS2, realizes the transformation of its semiconductor type from indirect to direct semiconductor, and then combines MoS2 with cadmium sulfide to obtain a MoS2 / CdS composite material with high photocatalytic performance. The MoS2 / CdS composite material synthesized by this method has high photocatalytic efficiency and its energy band position is consistent with H + The reduction potential matches that of the photocatalysts, which can effectively inhibit the recombination of photogenerated carriers and has excellent photocatalytic hydrogen production performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a SEM image of the MoS2 / CdS composite photocatalytic material prepared in Example 3; Figure 2 HRTEM image of the MoS2 / CdS composite photocatalytic material prepared in Example 3; Figure 3 The UV-visible absorption graph of MoS2 prepared in Examples 1-3 and Comparative Examples 2-3; Figure 4 is the Tauc plot of MoS2 prepared in Examples 1-3 and Comparative Examples 2-3; Figure 5 Graph showing the photocatalytic hydrogen production activity of the MoS2 / CdS composite materials prepared in Examples 1-4 and Comparative Examples 1-3. DETAILED DESCRIPTION

[0014] The above contents of the present invention are further described in detail below through examples, but the contents of the present invention are not limited thereto.

[0015] Example 1 A method for preparing an indirect / direct heterojunction MoS2 / CdS composite photocatalytic material (1) 0.1 g MoS2 and 0.04 g alumina were mixed, and 80 mL deionized water was added. Ultrasonic treatment was performed for 240 min. After the ultrasonic treatment, the mixture was allowed to stand for 24 h. The supernatant was collected and the concentration of MoS2 was 0.15 g / L. The ultraviolet absorption curve data was tested and the band gap of MoS2 was obtained as 1.58 eV according to the Kubelk-Munk formula.

[0016] (2) Take 0.1234 g of cadmium nitrate tetrahydrate, 0.304 g of thiourea, and 0.916 g of sodium citrate, and add them to 66.7 mL of MoS2 supernatant. The mass of MoS2 in the supernatant is 15% of the mass of the target product MoS2 / CdS. Add 1 mL of ammonia water and deionized water to make the total volume of the solution reach 70 mL. Stir at room temperature to form a uniform solution.

[0017] (3) Transfer the homogenous solution to a 100 mL polytetrafluoroethylene reactor, place the reactor in an oven, set the insulation temperature to 180 °C, and keep it warm for 18 h. After heating, wait for the reactor to cool naturally and then take it out to obtain the sample.

[0018] (4) The sample obtained in step (3) was separated by suction filtration, washed with deionized water for multiple times, and dried in an oven at 70°C for 12 h to obtain a yellow-black powder, namely, the MoS2 / CdS composite photocatalytic material.

[0019] The photolysis of water to produce hydrogen was carried out in a 150 mL reaction cell at room temperature and pressure. A 300 W xenon lamp was used as the light source and a UV cutoff filter (λ≥420 nm) was used to filter out ultraviolet light. In the experiment, 20 mg MoS2 / CdS was dispersed in a mixed solution of 80 mL deionized water and 20 mL lactic acid. The reaction temperature was kept at 6 °C by external circulating water. The solution was continuously stirred during the experiment to ensure that the catalyst could fully utilize the light energy. The generated gas was pumped into the gas chromatograph by a plunger pump. The photocatalytic performance of the prepared MoS2 / CdS composite material was 6.75 mmol· g -1 · h -1 .

[0020] Example 2 A method for preparing an indirect / direct heterojunction MoS2 / CdS composite photocatalytic material (1) 0.1 g MoS2 and 0.04 g alumina were mixed, and 80 mL deionized water was added. Ultrasonic treatment was performed for 480 min. After the ultrasonic treatment, the mixture was allowed to stand for 24 h. The supernatant was collected and the concentration of MoS2 was 0.17 g / L. The ultraviolet absorption curve data was tested and the band gap of MoS2 was obtained as 1.65 eV according to the Kubelk-Munk formula.

[0021] (2) Take 0.1234 g of cadmium nitrate tetrahydrate, 0.304 g of thiourea, and 0.916 g of sodium citrate, and add them to 58.8 mL of MoS2 supernatant. The mass of MoS2 in the supernatant is 15% of the mass of the target product MoS2 / CdS. Add 1 mL of ammonia water and deionized water to make the total volume of the solution reach 70 mL. Stir at room temperature to form a uniform solution.

[0022] (3) Transfer the homogenous solution to a 100 mL polytetrafluoroethylene reactor, place the reactor in an oven, set the insulation temperature to 180 °C, and keep it warm for 18 h. After heating, wait for the reactor to cool naturally and then take it out to obtain the sample.

[0023] (4) The sample obtained in step (3) was separated by suction filtration, washed with deionized water for multiple times, and dried in an oven at 70°C for 12 h to obtain a yellow-black powder, namely, the MoS2 / CdS composite photocatalytic material.

[0024] The photolysis of water to produce hydrogen was carried out in a 150 mL reaction cell at room temperature and pressure. A 300 W xenon lamp was used as the light source and a UV cutoff filter (λ≥420 nm) was used to filter out the ultraviolet light. In the experiment, 20 mg of the sample was dispersed in a mixed solution of 80 mL of deionized water and 20 mL of lactic acid. The reaction temperature was kept at 6 °C by external circulating water. The solution was continuously stirred during the experiment to ensure that the catalyst could fully utilize the light energy. The generated gas was pumped into the gas chromatograph by a plunger pump. The photocatalytic performance of the prepared MoS2 / CdS composite material was 7.22 mmol· g -1 · h -1 .

[0025] Example 3 A method for preparing an indirect / direct heterojunction MoS2 / CdS composite photocatalytic material (1) 0.1 g MoS2 and 0.04 g alumina were mixed, and 80 mL deionized water was added. Ultrasonic treatment was performed for 720 min. After the ultrasonic treatment, the mixture was allowed to stand for 24 h and the supernatant was collected. The concentration of MoS2 was 0.2 g / L. The ultraviolet absorption curve data was tested and the band gap of MoS2 was obtained as 1.71 eV according to the Kubelk-Munk formula.

[0026] (2) Take 0.1234 g of cadmium nitrate tetrahydrate, 0.304 g of thiourea, and 0.916 g of sodium citrate, and add them to 50 mL of MoS2 supernatant. The mass of MoS2 in the supernatant is 15% of the mass of the target product MoS2 / CdS. Add 1 mL of ammonia water and deionized water to make the total volume of the solution reach 70 mL. Stir at room temperature to form a uniform solution.

[0027] (3) Transfer the homogenous solution to a 100 mL polytetrafluoroethylene reactor, place the reactor in an oven, set the insulation temperature to 180 °C, and keep it warm for 18 h. After heating, wait for the reactor to cool naturally and then take it out to obtain the sample.

[0028] (4) The sample obtained in step (3) was separated by suction filtration, washed with deionized water for multiple times, and dried in an oven at 70°C for 12 h to obtain a yellow-black powder, MoS2 / CdS composite photocatalytic material.

[0029] The obtained MoS2 / CdS was characterized by scanning electron microscopy (SEM) and high-resolution transmission electron microscopy (HRTEM). Figure 1 is the SEM image of MoS2 / CdS. Figure 1 It can be seen that CdS grows uniformly on the MoS2 nanosheets. Figure 2 is the HRTEM image of the sample, Figure 2 It can be seen that the exfoliated MoS2 is flaky and has obvious lattice fringes. At the same time, there is an obvious boundary between CdS and MoS2.

[0030] The photolysis of water to produce hydrogen was carried out in a 150 mL reaction cell at room temperature and pressure. A 300 W xenon lamp was used as the light source and a UV cutoff filter (λ≥420 nm) was used to filter out the ultraviolet light. In the experiment, 20 mg of the sample was dispersed in a mixed solution of 80 mL of deionized water and 20 mL of lactic acid. The reaction temperature was kept at 6 °C by external circulating water. The solution was continuously stirred during the experiment to ensure that the catalyst could fully utilize the light energy. The generated gas was pumped into the gas chromatograph by a plunger pump. The photocatalytic performance of the prepared MoS2 / CdS composite material was 9.7 mmol·g -1 · h -1 .

[0031] Example 4 A method for preparing an indirect heterojunction MoS2 / CdS composite photocatalytic material (1) Mix 0.1 g MoS2 and 0.04 g alumina, add 80 mL deionized water, and sonicate for 960 min. After sonication, let stand for 24 h and take the supernatant. The concentration of MoS2 is 0.22 g / L. (2) Take 0.1234 g of cadmium nitrate tetrahydrate, 0.304 g of thiourea, and 0.916 g of sodium citrate, and add them to 45.5 mL of MoS2 supernatant. The mass of MoS2 in the supernatant is 15% of the mass of the target product MoS2 / CdS. Add 1 mL of ammonia water and deionized water to make the total volume of the solution reach 70 mL. Stir at room temperature to form a uniform solution.

[0032] (3) Transfer the homogenous solution to a 100 mL polytetrafluoroethylene reactor, place the reactor in an oven, set the insulation temperature to 180 °C, and keep it warm for 18 h. After heating, wait for the reactor to cool naturally and then take it out to obtain the sample.

[0033] (4) The sample obtained in step (3) was separated by suction filtration, washed with deionized water for multiple times, and dried in an oven at 70°C for 12 h to obtain a yellow-black powder, MoS2 / CdS composite photocatalytic material.

[0034] The photolysis of water to produce hydrogen was carried out in a 150 mL reaction cell at room temperature and pressure. A 300 W xenon lamp was used as the light source and a UV cutoff filter (λ≥420 nm) was used to filter out the ultraviolet light. In the experiment, 20 mg of the sample was dispersed in a mixed solution of 80 mL of deionized water and 20 mL of lactic acid. The reaction temperature was kept at 6 °C by external circulating water. The solution was continuously stirred during the experiment to ensure that the catalyst could fully utilize the light energy. The generated gas was pumped into the gas chromatograph by a plunger pump. The photocatalytic performance of the prepared MoS2 / CdS composite material was 7.14 mmol· g -1 · h -1 .

[0035] Example 5 A method for preparing an indirect / direct heterojunction MoS2 / CdS composite photocatalytic material (1) 0.1 g MoS2 and 0.04 g alumina were mixed, and 80 mL deionized water was added. Ultrasonic treatment was performed for 720 min. After the ultrasonic treatment, the mixture was allowed to stand for 24 h. The concentration of MoS2 was 0.2 g / L. (2) Take 0.1234 g of cadmium nitrate tetrahydrate, 0.0608 g of thiourea, and 0.916 g of sodium citrate, and add them to 30 mL of MoS2 supernatant. The mass of MoS2 in the supernatant is 10% of the mass of the target product MoS2 / CdS. Add 1 mL of ammonia water and deionized water to make the total volume of the solution reach 70 mL. Stir at room temperature to form a uniform solution.

[0036] (3) Transfer the homogenous solution to a 100 mL polytetrafluoroethylene reactor, place the reactor in an oven, set the insulation temperature to 180 °C, and keep it warm for 18 h. After heating, wait for the reactor to cool naturally and then take it out to obtain the sample.

[0037] (4) The sample obtained in step (3) was separated by suction filtration, washed with deionized water for multiple times, and dried in an oven at 70°C for 12 h to obtain a yellow-black powder, namely, the MoS2 / CdS composite photocatalytic material.

[0038] The photolysis of water to produce hydrogen was carried out in a 150 mL reaction cell at room temperature and pressure. A 300 W xenon lamp was used as the light source and a UV cutoff filter (λ≥420 nm) was used to filter out the ultraviolet light. In the experiment, 20 mg of the sample was dispersed in a mixed solution of 80 mL of deionized water and 20 mL of lactic acid. The reaction temperature was kept at 6 °C by external circulating water. The solution was continuously stirred during the experiment to ensure that the catalyst could fully utilize the light energy. The generated gas was pumped into the gas chromatograph by a plunger pump. The photocatalytic performance of the prepared MoS2 / CdS composite material was 6.75 mmol· g -1 · h -1 .

[0039] Example 7 A method for preparing an indirect / direct heterojunction MoS2 / CdS composite photocatalytic material (1) 0.1 g MoS2 and 0.04 g alumina were mixed, and 80 mL deionized water was added. Ultrasonic treatment was performed for 720 min. After the ultrasonic treatment, the mixture was allowed to stand for 24 h. The concentration of MoS2 was 0.2 g / L. (2) Take 0.1234 g of cadmium nitrate tetrahydrate, 0.152 g of thiourea, and 0.916 g of sodium citrate, add them to 70 mL of MoS2 supernatant, the mass of MoS2 in the supernatant is 20% of the mass of the target product MoS2 / CdS, and add 1 mL of ammonia water, and stir at room temperature to form a uniform solution.

[0040] (3) Transfer the homogenous solution to a 100 mL polytetrafluoroethylene reactor, place the reactor in an oven, set the insulation temperature to 180 °C, and keep it warm for 18 h. After heating, wait for the reactor to cool naturally and then take it out to obtain the sample.

[0041] (4) The sample obtained in step (3) was separated by suction filtration, washed with deionized water for multiple times, and dried in an oven at 70°C for 12 h to obtain a yellow-black powder, namely, the MoS2 / CdS composite photocatalytic material.

[0042] The photolysis of water to produce hydrogen was carried out in a 150 mL reaction cell at room temperature and pressure. A 300 W xenon lamp was used as the light source and a UV cutoff filter (λ≥420 nm) was used to filter out the ultraviolet light. In the experiment, 20 mg of the sample was dispersed in a mixed solution of 80 mL of deionized water and 20 mL of lactic acid. The reaction temperature was kept at 6 °C by external circulating water. The solution was continuously stirred during the experiment to ensure that the catalyst could fully utilize the light energy. The generated gas was pumped into the gas chromatograph by a plunger pump. The photocatalytic performance of the prepared MoS2 / CdS composite material was 7.5 mmol·g -1 · h -1 .

[0043] Example 8 A method for preparing an indirect / direct heterojunction MoS2 / CdS composite photocatalytic material (1) Take 0.1234 g of cadmium nitrate tetrahydrate, 0.304 g of thiourea, and 0.916 g of sodium citrate, and add them to 50 mL of MoS2 supernatant synthesized under the same conditions as in Example (3), where the mass of MoS2 in the supernatant is 15% of the mass of the target product MoS2 / CdS, and add 1 mL of ammonia water. Add deionized water to make the total volume of the solution reach 70 mL, and stir at room temperature to form a uniform solution.

[0044] (3) Transfer the homogenous solution to a 100 mL polytetrafluoroethylene reactor, place the reactor in an oven, set the insulation temperature to 200 °C, and keep it warm for 24 h. After heating, wait for the reactor to cool naturally and then take it out to obtain the sample.

[0045] (4) The sample obtained in step (3) was separated by suction filtration, washed with deionized water for multiple times, and dried in an oven at 70°C for 12 h to obtain a yellow-black powder, MoS2 / CdS composite photocatalytic material.

[0046] Example 9 A method for preparing an indirect / direct heterojunction MoS2 / CdS composite photocatalytic material (1) Take 0.1234 g of cadmium nitrate tetrahydrate, 0.304 g of thiourea, and 0.916 g of sodium citrate, and add them to 50 mL of MoS2 supernatant synthesized under the same conditions as in Example (3), where the mass of MoS2 in the supernatant is 15% of the mass of the target product MoS2 / CdS, and add 1 mL of ammonia water. Add deionized water to make the total volume of the solution reach 70 mL, and stir at room temperature to form a uniform solution.

[0047] (3) Transfer the homogenous solution to a 100 mL polytetrafluoroethylene reactor, place the reactor in an oven, set the insulation temperature to 180 °C, and keep it warm for 12 h. After heating, wait for the reactor to cool naturally and then take it out to obtain the sample.

[0048] (4) The sample obtained in step (3) was separated by suction filtration, washed with deionized water for multiple times, and dried in an oven at 70°C for 12 h to obtain a yellow-black powder, MoS2 / CdS composite photocatalytic material.

[0049] Comparative Example 1 A method for preparing CdS photocatalytic material (1) Take 0.1234 g of cadmium nitrate tetrahydrate, 0.304 g of thiourea, and 0.916 g of sodium citrate, add 1 mL of aqueous ammonia, and add deionized water to make the total volume of the solution reach 70 mL. Stir at room temperature to form a uniform solution.

[0050] (2) Transfer the solution to a 100 mL polytetrafluoroethylene reactor and place the reactor in an oven at 180 °C for 18 h. After heating, cool the reactor and take it out.

[0051] (3) The obtained sample was separated by suction filtration, washed with deionized water for several times, and dried in an oven at 70 °C for 12 h. The obtained sample was a yellow powder.

[0052] The photolysis of water to produce hydrogen was carried out in a 150 mL reaction cell at room temperature and pressure. A 300 W xenon lamp was used as the light source and a UV cutoff filter (λ ≥ 420 nm) was used to filter out the ultraviolet light. In the experiment, 20 mg of CdS sample was dispersed in a mixed solution of 80 mL of deionized water and 20 mL of lactic acid. The reaction temperature was kept at 6 °C by external circulating water. The solution was continuously stirred during the experiment to ensure that the catalyst could fully utilize the light energy. The generated gas was pumped into the gas chromatograph by a plunger pump. The photocatalytic performance of the prepared cadmium sulfide was 1.13 mmol· g -1 · h -1 .

[0053] Comparative Example 2 A method for preparing MoS2 / CdS composite photocatalytic material (1) Take 0.1234 g of cadmium nitrate tetrahydrate, 0.304 g of thiourea, 0.916 g of sodium citrate, and 0.01 g of molybdenum disulfide powder, add 1 mL of ammonia water, and add deionized water to make the total volume of the solution reach 70 mL. Stir at room temperature to form a uniform solution.

[0054] (2) Transfer the solution to a 100 mL polytetrafluoroethylene reactor and place the reactor in an oven at 180 °C for 18 h. After heating, cool the reactor and take it out.

[0055] (3) The obtained sample was separated by suction filtration, washed with deionized water for several times, and dried in an oven at 70 °C for 12 h. The obtained sample was a yellow-black powder.

[0056] The photolysis of water to produce hydrogen was carried out in a 150 mL reaction cell at room temperature and pressure. A 300 W xenon lamp was used as the light source and a UV cutoff filter (λ≥420 nm) was used to filter out ultraviolet light. In the experiment, 20 mg of MoS2 / CdS sample was dispersed in a mixed solution of 80 mL of deionized water and 20 mL of lactic acid. The reaction temperature was kept at 6 °C by external circulating water. The solution was continuously stirred during the experiment to ensure that the catalyst could fully utilize the light energy. The generated gas was pumped into the gas chromatograph by a plunger pump. The photocatalytic performance of the prepared MoS2 / CdS composite material was 3.51 mmol· g -1 · h -1 .

[0057] Comparative Example 3 A method for preparing direct / direct heterojunction MoS2 / CdS composite photocatalytic material (1) 0.1 g MoS2 and 0.04 g alumina were mixed, and 80 mL deionized water was added. Ultrasonic treatment was performed for 1200 min. After the ultrasonic treatment, the mixture was allowed to stand for 24 h and the supernatant was collected. At this time, the MoS2 in the supernatant was a direct semiconductor and the concentration of MoS2 was 0.24 g / L. The ultraviolet absorption curve data was tested and the band gap of MoS2 was obtained as 1.75 eV according to the Kubelk-Munk formula.

[0058] (2) Take 0.1234 g of cadmium nitrate tetrahydrate, 0.304 g of thiourea, and 0.916 g of sodium citrate, and add them to 41.7 mL of MoS2 supernatant. The mass of MoS2 in the supernatant is 15% of the mass of the target product MoS2 / CdS. Add 1 mL of ammonia water and deionized water to make the total volume of the solution reach 70 mL. Stir at room temperature to form a uniform solution.

[0059] (3) Transfer the homogenous solution to a 100 mL reactor, place the reactor in an oven, set the insulation temperature to 180 °C, and keep it warm for 18 h. After heating, cool the reactor and take it out to obtain the sample.

[0060] (4) The sample obtained in step (3) was separated by suction filtration, washed with deionized water for multiple times, and dried in an oven at 70°C for 12 h. The obtained sample was a yellow-black powder, i.e., a MoS2 / CdS composite photocatalytic material.

[0061] The photolysis of water to produce hydrogen was carried out in a 150 mL reaction cell at room temperature and pressure. A 300 W xenon lamp was used as the light source and a UV cutoff filter (λ≥420 nm) was used to filter out the ultraviolet light. In the experiment, 20 mg of the sample was dispersed in a mixed solution of 80 mL of deionized water and 20 mL of lactic acid. The reaction temperature was kept at 6 °C by external circulating water. The solution was continuously stirred during the experiment to ensure that the catalyst could fully utilize the light energy. The generated gas was pumped into the gas chromatograph by a plunger pump. The photocatalytic performance of the prepared MoS2 / CdS composite material was 3.62 mmol·g -1 · h -1 .

[0062] Figure 3 is the ultraviolet absorption diagram of molybdenum disulfide at different ultrasonic times of the present invention, Figure 3 It can be seen that with the increase of ultrasound time, the absorption capacity of molybdenum disulfide for visible light becomes stronger and stronger.

[0063] Figure 4 is based on Figure 3 The data in the figure are used to calculate the Tauc diagram using the Kubelk-Munk formula. The band gap of MoS2 at different ultrasonic times is obtained based on the Tauc diagram. Figure 4 It can be seen that with the increase of ultrasonic time, the band gap of MoS2 gradually widens. When the ultrasonic time reaches 20 h, as the ultrasonic time further increases, the semiconductor properties of MoS2 change from indirect semiconductor to direct semiconductor. At this time, the lifetime of photogenerated carriers becomes shorter and the recombination intensifies, resulting in a decrease in photocatalytic performance.

[0064] Figure 5 is a photocatalytic performance diagram of MoS2 / CdS synthesized in the present invention, Figure 5 It can be seen that among the MoS2 / CdS catalysts synthesized in the present invention, the sample synthesized in Example 3 has the highest hydrogen production rate, with a photocatalytic hydrogen production rate of 9.7 mmol·g -1 · h -1 The performance of pure CdS in comparative example 1 is 1.13 mmol· g -1 · h -1 The performance of cadmium sulfide / unulterated molybdenum disulfide in comparative example 2 is 3.51 mmol· g -1 · h -1The photocatalytic hydrogen production rate of the sample obtained in Comparative Example 3 is 3.62 mmol·g -1 · h -1 .

Claims

1. A method for preparing an indirect / direct heterojunction MoS2 / CdS composite photocatalytic material, characterized in that: The specific steps of the preparation method are as follows: (1) MoS2 and alumina abrasive were mixed, deionized water was added for ultrasonic treatment, and then the mixture was allowed to stand to collect the supernatant; (2) adding cadmium nitrate tetrahydrate, thiourea and sodium citrate to the supernatant obtained in step (1), and sequentially adding ammonia water and deionized water, and stirring at room temperature to form a uniform solution; (3) The uniform solution was transferred to a polytetrafluoroethylene reactor, and the reactor was placed in an oven to keep warm. After natural cooling, the reactor was taken out and the obtained sample was separated by filtration, washed with deionized water for multiple times, and placed in an oven to dry to obtain a MoS2 / CdS composite photocatalytic material.

2. The preparation method according to claim 1, characterized in that In the step (1), the mass ratio of MoS2 to alumina is 1:0.2-1:0.6; the mass volume ratio of MoS2 to deionized water is 1:600-1000, g / mL.

3. The preparation method according to claim 2, characterized in that In the step (1), the mass ratio of MoS2 to alumina is 1:0.4; the mass volume ratio of MoS2 to deionized water is 1:800, g / mL.

4. The preparation method according to claim 1, characterized in that In the step (1), the ultrasonic time is t, 4≤t<20, preferably 12 h; and the standing time is 24-48 h.

5. The preparation method according to claim 1, characterized in that In the step (2), the molar ratio of cadmium nitrate tetrahydrate to thiourea is 1:1-1:10; the concentration of sodium citrate in the homogeneous solution is 0.6-2 mg / mL; the volume fraction of ammonia water is 0.7-3% of the homogeneous solution; and the mass of MoS2 added to the supernatant is 10-20% of the mass of the target product MoS2 / CdS.

6. The preparation method according to claim 5, characterized in that: In step (2), the volume fraction of aqueous ammonia is 1.3% of the homogeneous solution; the mass of MoS2 added to the supernatant is 15% of the mass of the target product MoS2 / CdS.

7. The preparation method according to claim 1, characterized in that The insulation temperature in step (3) is 180-220° C., and the insulation time is 12-24 h.

8. The preparation method according to claim 1, characterized in that The drying temperature in step (3) is 70°C and the drying time is 12 h.

9. The indirect / direct heterojunction MoS2 / CdS composite photocatalytic material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the indirect / direct heterojunction MoS2 / CdS composite photocatalytic material as claimed in claim 9 in photocatalytic water decomposition to produce hydrogen.

Citation Information

Patent Citations

  • Molybdenum disulfide-cadmium sulfide nanocomposites, their preparation methods and applications

    CN105664977B

  • Cadmium sulfide nanoparticle / molybdenum disulfide nanobelt heterostructure catalyst for hydrogen production by water decomposition under visible light and preparation method thereof

    CN111229260A

Cited By

  • A zoned gradient polarization electric field induced p-i-n-like stacked photocatalyst and a preparation method thereof

    CN122850197A

  • Cadmium sulfide photocatalyst based on gradient concentration cadmium vacancy induced ordered phase polarization electric field, and preparation method and application thereof

    CN122875253A